FOSTERING ORAL PROFICIENCY THROUGH STORY COMPLETION IN LANGUAGE DEVELOPMENT UNIT CLASS - Nor, Hidayah; Aulia, Insan; Rahman, Muhammad Arinal (University of Darussalam Gontor, 2024)
The purpose of this descriptive qualitative study was to investigate the application of the storycompletion technique to foster students’ speaking proficiency and to pinpoint the difficulties thatarise when doing the activities. An English tutor from Antasari State Islamic University's LanguageDevelopment Unit, group 31, who works with eighteen students of different majors selected basedon the purposive random sampling technique, participated in the study. Semi-structured interviewsand observations were used to gather the data then analyzed by using Miles and Huberman’s theorywhich consisted of data reduction, data display, and drawing the conclusion. The results provide astep-by-step procedure for applying the story completion technique, which includes determining thevocabulary and grammar that students have acquired, choosing an appropriate topic, evaluatingstudents' fluency in the target language, a suitable story topic is chosen, the class is arranged in acircle, the story is started, and it ends after a few sentences. Students then take turns continuing thestory, adding one to three sentences at a time. They are also free to add new characters, events, anddescriptions to the story, and it continues until a logical conclusion or student intervention occurs.Apart from that, the study brought to light several obstacles, including choosing stories that studentscan relate to, handling big class sizes, handling time limits, addressing personal issues, as well asevaluating and giving feedback to students. The knowledge gathered from this study helps to clarifyhow the story completion technique is used to develop speaking skills and offers helpful suggestionsto language teachers on how to deal with the difficulties encountered while applying this technique.All things considered; the study's findings have a great deal to offer language teachers throughoutthe globe in terms of practical advice on how to improve language acquisition using interactivestorytelling techniques while resolving typical challenges that arise in bilingual settings.